Transformasi Sosial terhadap Kebijakan Pengelolaan Bank NTT (Studi Kasus pada Kantor Pusat Bank NTT di Kota Kupang) - Rahmat Saleh; Ahmad Atang; Rahmat Laan; Syarifuddin Darajat (Universitas Hamzanwadi, 2026)
This study aims to describe and examine in depth the forms of social transformation and their impacts on the management policies of Bank NTT. The research employs a qualitative approach, with data collected through observation, interviews, and document analysis. The data were analyzed using descriptive qualitative methods. The theoretical frameworks applied in this study are structural functionalism and systems theory. The findings indicate that transformation at Bank NTT represents a process of systemic change centered on digitalization and human resources, which has broadly affected organizational structure, work patterns, and employee work culture. Digital transformation at Bank NTT has been driven by demands for increased operational efficiency, service expansion, and the need to adapt to societal behavior that is increasingly dependent on digital technology. Social transformation and management policies at Bank NTT have generated positive impacts, as reflected in improved work efficiency and effectiveness, enhanced quality of customer service, strengthened employee professionalism and accountability, as well as the modernization of work systems and organizational governance. Nevertheless, several negative impacts were also identified, including resistance to change among some employees, increased work pressure and adaptation burdens, gaps in technological competencies, and tensions in workplace relations during the transition period. Theoretically, these findings are relevant to structural functionalism and systems theory, as the success or failure of transformation depends on the support of subsystems and the effective functioning of existing structures within Bank NTT that sustain social transformation and its management policies.